2006
DOI: 10.1128/jcm.44.3.1175-1177.2006
|View full text |Cite
|
Sign up to set email alerts
|

Use of DNA Sequencing Analysis To Confirm Fungemia Due to Trichosporon dermatis in a Pediatric Patient

Abstract: This is the first reported case of human disease caused by Tricosporon dermatis, an organism recently transferred to the genus Trichosporon from Cryptococcus and now confirmed to be a human pathogen. CASE REPORTA 13-month-old male with a history of autoimmune enteropathy developed a fever of unknown origin (FUO) and malaise. The patient was the product of a full-term uncomplicated pregnancy and delivery. At 9 days of life he had a rotavirus infection and subsequently developed a malabsorption-dysmotility syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
23
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
4
23
0
3
Order By: Relevance
“…The genus Trichosporon now comprises 36 species. The number of Trichosporon species causing disseminated disease is expanding; T. asteroides, T. loubieri, and T. dermatis have recently been shown to cause disseminated trichosporonosis (25,33,38,55). Trichosporon has been reported to be the most common cause of nonCandida yeast infections in patients with hematological malignancies, and the infections were associated with high mortality rates, despite antifungal therapy (59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Trichosporon now comprises 36 species. The number of Trichosporon species causing disseminated disease is expanding; T. asteroides, T. loubieri, and T. dermatis have recently been shown to cause disseminated trichosporonosis (25,33,38,55). Trichosporon has been reported to be the most common cause of nonCandida yeast infections in patients with hematological malignancies, and the infections were associated with high mortality rates, despite antifungal therapy (59).…”
Section: Discussionmentioning
confidence: 99%
“…Although uncommon, pathogenic species of this genus have been reported increasingly, mostly in patients with malignant diseases (3,6,9,10,11,20,32,44,47,48,63,77), neonates (18,56,84), a bone marrow transplant recipient (22), a solid organ transplant recipient (50), and patients with human immunodeficiency virus (34,35,46). Trichosporon has also been reported to cause fungemia (5,9,25,29,30,33,53,62). Members of the genus Trichosporon have occasionally been implicated as nail pathogens (16,28,74) and in subcutaneous infections (66).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been mentioned in the literature that an isolate identified by molecular methods as Trichosporon dermatis was mistakenly identified as Trichosporon mucoides when Vitek Systems 1 and 2 (BioMérieux, France) were used (16). Furthermore, Ahmad et al (1) reported that four isolates previously identified by Vitek 2 as Trichosporon asahii were identified as Trichosporon asteroides by molecular techniques.…”
mentioning
confidence: 99%
“…Trichosporonosis is recognized as one of the emerging opportunistic mycosis in tertiary care hospitals, worldwide (8,9). These non-Candida yeasts present varied clinical manifestations ranging from superficial infections to severe life threatening invasive diseases in the immunocompromised host (10).…”
Section: Discussionmentioning
confidence: 99%